Uma história da primeira estação ferroviária de Aracaju (1910-1976) - Jesus, André Luiz Sá de (2017)
The research builds the history of the First Train Station of Aracaju, between the years 1910 and 1976. The year 1910 marks the appearing of documented information about the construction site of the Train Station; 1976 was the year the City Council ordered that Station to be demolished. The First Train Station was located in downtown Aracaju, near the Port. The importance of our research lies in the fact that the Train Station building has not been deeply studied yet and besides it no longer exists. The objective of the research is an historical data survey on the First Train Station of Aracaju, displaying several social, historical and economic aspects regarding that building, from 1910 to 1976. In the research we used secondary sources such as novels and memorial books, and primary documentation such as local newspapers and vintage photographs. The investigation shows the Station as a main point of a rail network in Sergipe, connected to the Brazilian railroad. During its operation, from 1913 to 1950, the First Station registered an intense flow of people from several social classes. Economically speaking, the Station had a strategic location, being directly linked to the Port of Aracaju and being next to various fabric factories and warehouses, allowing an expressive flow of animals, agricultural products and manufactured goods. While boosting its surroundings development, the Station may have attracted the construction of new commercial and public buildings. However, after losing its strategic importance due to the opening of the new Station of Siqueira Campos, the First Station was gradually abandoned, favoring the emerging of shacks nearby, with poor people living in precarious conditions, so the City Council provided the slum to be removed and to have the Station demolished. Finally the research intends to make an important contribution to the railroad history in Brazil as well as to Aracaju and the State of Sergipe history.